Input Sensors with PLC: 4-20 mA Current Loop. - Khalil, Zara (linkedin.com, 2024)
Learn about the 4-20mA current loop circuit and its components, a circuit used when connecting analog industrial sensors to PLCs (programmable logic controllers.